Bentonite and RHA Adsorption Performance Against Characteristics Waste-Cooking Oil - Hidayat, Jefri Pandu; Hariyad, Asful; Chosta, Fidela (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2022)
Cooking oil is one of basic needs among human that develop year by year. The potency of waste-cooking oil utilization is unique study section. The purpose was reused waste-cooking oil become the ready matter by adsorption method. Effectiveness test adsorben between bentonite and rice husk ash (RHA) on used cooking oil was carried out in three stages which consist of characterization raw material, adsorption process, and feasibility test. The characterization stage was figured out in some parameters, clarity level (absorbance), density, moisture content, acid value, and peroxide number, metal element (Cu, Fe, and Pb). One-way analysis of variance (ANOVA) was performed between additive weight and adsoprtion time. Acid and peroxide number was tested by titrimetric method whereas the clarity level was examined with UV-Vis Spectrometry based on absorbance value. The optimum condition was the addition 55 gram bentonite for 40 minute treatment with absorbance, acid, and peroxide number 0,227; 0,443 mg/g; 0,986 mg/g respectively. The oil regeneration characteristics have meet the SNI (3741:2013) requirements however peroxide number still in limitance. Further, the study was required to develop edible oil properties toward the materials and adsorption method modification.